Patterns And Concepts Of Teacher Strategies In Forming Student Character In The Technological Era (Analysis Study With A Systematic Literature Review Approach) - Latif Syaipudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The aim of this research is to find out how strategic planning, implementation and evaluation of learning shape student character in the technological era in carrying out learning activities. The research method uses a literature review with descriptive analysis, the data collected is secondary data or comes from several journals and research that are relevant to the research study. The results of this research show that teachers' strategic planning in learning activities to shape students' character in the digital era is carried out to instill human values that instill good character, morals and behavior in a person which is reflected in their behavior. Implementation of learning strategies in shaping student character in the digital era can also be done through the delivery of learning materials, however, in the process of evaluating teachers' learning strategies, they need improvement because there are still many teachers who are not yet able to utilize technology as a learning aid. The teacher is one of the most crucial and dominant figures who will have a direct impact on the success of students, both in terms of quantity and quality of learning. Strategy is an important part that cannot be separated, so teachers must also determine the right strategy.